Di-n-butyl{1-[1-(2-hydroxyphenyl)ethylidene]-5-[1-(2-oxidophenyl)et hylidene]thiocarbazonato-kappa O-3(5),N-5,S}tin(IV) - Abu Affan, M.; Chee, D.N.A.C.; Assim, Z.; Ng, S.W. (International Union of Crystallography, 2010)
The `symmetrical' 1,5-bis[1-(2-hydroxyphenyl)ethylidene] thiocarbazone Schiff base condenses with dibutyltin oxide to form the title complex, [Sn(C4H9)(2)(C17H16N4O2S)],in which the deprotonated ligand O,N,S-chelates to the Sn atom of two crystallographically independent molecules. The ligand bears a formal negative charge on the S and one O atom; the other O atom retains its H atom. The Sn atoms are five-coordinated in a cis-C2NOSSn trigonal-bipyramidal environment, and the apical sites are occupied by the O and S atoms. In both molecules, the hydroxy group is hydrogen bonded to a double-bonded N atom, generating a six-membered ring. The amino group is a donor to the coordinated O atom of an adjacent molecule, the hydrogen-bonding interaction giving rise to a helical chain running along the b axis. In one of the independent molecules, the atoms of one of the n-butyl groups are disordered over two sets of sites with equal occupancy. In the other independent molecule, the atoms of both n-butyl groups are disordered over two sets of sites with equal occupancy and, in addition, the Sn and S atoms were also refined as disordered over two sets of sites with equal occupancy.